Clinical Outcome in Patients with Pulmonary Aspergilloma Undergoing Lung Resection: A Retrospective Cohort Study - Thiruvenkadam Selvaraj; Karthikeyan Govindaswamy; Vijayakumar Natarajan; Kumar Natarajan (Journal of Clinical and Diagnostic Research)
Introduction: Pulmonary aspergilloma occurs due to colonisation of previously present lung cavities by Aspergillus fumigatus. Surgery is one of the prime modalities of treatment, but there is paucity of data, dearth of knowledge in literature. Therefore, this study was conducted to study clinical outcome in patients with pulmonary aspergilloma undergoing lung resection. Aim: To find out clinical outcome, presentations and pre-existing lung diseases in patients with pulmonary aspergilloma. Materials and Methods: The present retrospective cohort study was done in patients with pulmonary aspergilloma treated surgically between January 2018 and December 2024 in tertiary care centre. Clinical outcome was assessed in terms of morbidity using postoperative complications and mortality. Analysis was done using Chi-square test, Statistical Package for Social Sciences (SPSS) version 23. Results: The total number of patients studied was 52. The mean age of study population was 42.7 years. In 46 (88.46%) the pre-existing lung disease was post tuberculous cavity followed by bronchiectasis in 4 (7.69%) and healed lung abscess in 2 (3.84%). Frank haemoptysis was the main presenting symptom in 47 patients (90.38%). Right upper lobe was involved in 34 (65.38%). Left upper lobe was involved in 16 (30.77%). Left lower lobe was involved in 1 (1.92%) and right middle lobe was involved in 1 (1.92%). Lobectomy was done in 51 (98.08%). Segmentectomy was done in 1 (1.92%). Bronchopleural fistula was the major complication seen in 7 (13.46%) followed by wound infection in 5 (9.61%) and empyema in 4 (7.69%). Statistically significant p-value (0.047) was found between postoperative complications and duration of hospital stay. Conclusion: Surgical resection is the best modality of treatment for pulmonary Aspergilloma. We recommend early surgical resection for good outcome. Preoperative lung optimisation, meticulous surgical technique and good postoperative care with physiotherapy reduced the rate of complications.